Implementation of Male Family Planning Policy Education with Surgical Methods in Men as Reproductive Health Learning - Wida Widiawati; Indriyati Kamil (Global Education Journal, 2025)
One of the main problems in the Family Planning (FP) program in Sumedang Regency is the low participation of men, especially in the use of the Male Operative Method (MOP) or vasectomy. The contributing factors include limited public knowledge, the stigma against MOP, and the lack of education and access to service facilities. This study aims to analyze the implementation of the male family planning service policy using the Male Operative Method in Jatinangor District, Sumedang Regency, with a focus on policy effectiveness, inhibiting factors, and strategies for optimizing male family planning services. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. Research informants consisted of health workers, family planning field officers (PLKB), Family Planning Assistant Cadres, and male family planning acceptors who use the MOP method. Data analysis was carried out interactively through data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that the implementation of the male family planning service policy using the MOP method in Jatinangor District has been implemented, but still faces challenges. The main inhibiting factors include limited access to services, limited public understanding of male family planning, a lack of trained medical personnel, and suboptimal coordination between agencies. However, there are also supporting factors, such as supportive government policies and the active role of family planning counselors in several villages.